Tuning Block Polymer Structure, Properties, and Processability for the Design of Efficient Nanostructured Materials Systems. Issue 5 (24th January 2017) - Morris, Melody A.; Gartner, Thomas E.; Epps, Thomas H.
Abstract : Block polymers (BPs) are complex materials with the ability to self‐assemble on nanometer lengthscales. This article details the Epps group's work on manipulating the macromolecular interactions in BPs in both bulk and thin film systems to improve control of ordering, orientation, processing, and properties. These developments will facilitate the continued incorporation of BPs in energy storage devices, microelectronic templating, and other technologies. Abstract : Block polymers (BPs) are ideal building blocks for nanoporous membranes, microelectronics templates, energy storage devices, and other technologies. For these systems, precise control over morphology, properties, and processability are essential to optimize performance. The Epps group has used a multidisciplinary approach to control BP nanostructure ordering and orientations, order‐disorder and glass transition temperatures, and mechanical and transport properties through the informed manipulation of BP effective segregation strengths and interfacial energetics. For example, alterations in macromolecular interactions between BP chains were achieved through the introduction of composition gradients between copolymer blocks or by adding dopants. In thin films, high‐throughput approaches were designed to modify and characterize substrate‐polymer interactions, and solvent annealing techniques were developed to facilitate nanoscale alignment and ordering. By manipulating BP interfacial energetics to gain exquisite tunability of nanostructures and materials' properties, the group is accelerating the development of next‐generation BPs that will be harnessed to fabricate inexpensive, efficient, and high‐performance devices.